KUALITAS KEBERSIHAN KAMAR TAMU DI HOTEL X - Primantara, I Gede Bagus Mahardika; Adi, Ida Ayu Sri Puspa; Launingtia, I Gusti Ayu Niken (Program Studi Manajemen Divisi Kamar, 2025)
This study aims to assess the quality of guest room hygiene at Hotel X. A descriptive qualitative research method was used, with data collected through observations and interviews. The results indicate that 80% of the guest rooms at Hotel X meet the established hygiene standards, while 20% do not comply with these standards. Based on these findings, the following recommendations are proposed: Housekeeping management should reconsider the time allocation and room assignments per section to ensure that room attendants are not rushed during the cleaning process. This would allow them to maintain optimal cleanliness standards. Housekeeping management should implement a periodic maintenance plan for repairing furniture and equipment in certain rooms, ideally during low occupancy periods (low season). This approach aims to enhance overall guest room hygiene quality. Room attendants should conduct a final inspection after cleaning each room to verify that it meets cleanliness standards and is properly prepared as a